Legality of Appointment of Village Apparatus according to Article 49 Paragraph (2) of Law Number 6 of 2014 concerning Villages in Ujung Padang Village, Alas Maras Subdistrict, Seluma Regency - Jenzen Idianza; Sandi Aprianto; M. Arafat Hermana (JURNAL HUKUM SEHASEN, 2022)
The purpose of this study was to determine the procedures for the appointment of old village officials and new village officials in the village of Ujung Padang and to find out the validity of the appointment of old and new village officials in the village of Ujung Padang in terms of Law Number 6 of 2014. The research method in this paper is the method Qualitative research is research that refers to the legal norms contained in legislation and court decisions as well as norms that live and develop in society. Based on the results of an interview with the Ujung Padang Village Head on July 5, 2022, he explained that, "If we talk about the mechanism for the appointment of village officials, of course the appointment of new and old Village officials is based on the law (Law number 6 of 2014 concerning Villages). ). Only the appointment of the Lamo Village Apparatus used to be filled with direct appointments by the Village Head and in consultation with the Camat, for the appointment of the New Village Apparatus I carried out the Undnag-Undnag Mandate Number 6 of 2014 and the Seluma Regional Government Number 7 of 2016 regarding Village Apparatus. Fill it out through a screening and screening mechanism, selection of prospective candidates, and a written test. After getting the results of the selection then communicated with the Camat on behalf of the Regent. If we talk about the legal legitimacy of the official Village apparatus, both the old and the new, it is certainly not our domain to determine the legal person, and the one who is nedo is legal. That is the realm of the State Administrative Court, which can determine you.”